ANALISIS PEMAHAMAN TAJHIZ MAYIT PADA GENERASI MILLENIALS KOTA MEDAN - Said Rizal; Zulkifli Taib; Suratni Afrianti (Edudeena : Journal of Islamic Religious Education, 2020)
Abstract:  The study aims to find out Tajhiz Mayit's understanding on generations of Millennial in Medan City. Generations of Millennial are the next generation, they must certainly open a space of consciousness thinking that life in this world is only temporary and will be held accountable for what has been done so as not to be neglected with this mortal world by the evidence "Kullu Nafsin Djaiqotul death" (every one who must have suffered death). Focus in the study in the form of (1) Knowing the understanding Tajhiz Mayit on the generation of Millennial of the city of Medan, (2) How the efforts of generations of Millennial to learn the ordinances of Tajhiz Mayit, (3) What obstacles were faced by millennial in understanding Tajhiz Mayit. This research uses the method of a Kulaitatif descriptive through Observation, Interviu, Polls, and Documentation Studies. It can be found the research results that generation Millennial, at the level of the theory and concept is obtained at the education bench at school, campus, book reading, Media, and training conducted youth mosque, religious figures and community leaders who organized, but only on the level of theory but at the management procedure Tajhiz Mayit has not been practiced directly, so taken over by Youth Mosque (Bilal) to carry out. The draft of this research to provide the recommendation of Medan City development in policy taking on the Program can observe the religious education of Millennial.   Abstrak: Penelitian ini bertujuan untuk mengetahui Pemahaman Tajhiz Mayit Pada Generasi Millenial Kota Medan. Generasi Millenial merupakan generasi penerus, suda tentunya harus membuka ruang kesadaran berfikir bahwa hidup didunia ini hanya bersifat sementara dan akan dimintai pertanggungjawaban apa yang telah diperbuat sehingga tidak terlena dengan dunia yang fana ini dengan dalil "Kullu Nafsin Djaiqotul Maut" (Setiap yang beryawa pasti mengalami kematian). Fokus dalam penelitian ini berupa (1) Mengetahui Pemahaman Tajhiz Mayit Pada Generasi Millenial Kota Medan, (2) Bagaimana Upaya Generasi Millenial Untuk Mempelajari Tata Cara Tajhiz Mayit, (3) Kendala Apa Saja Yang di Hadapi Generasi Millenial Dalam Pemahaman Tajhiz Mayit. Penelitian ini menggunakan Metode Deskriptif Kulaitatif melalui Observasi, Wawancara, angket, dan Studi Dokumentasi. Dapat ditemukan hasil penelitian bahwa Generasi Millenial, Pada tataran Teori dan Konsep suda didapat pada bangku Pendidikan di Sekolah, Kampus, Bacaan Buku, Media, maupun Pelatihan yang dilakukan Remaja Mesjid, Tokoh Agama dan Tokoh Masyarakat yang menyelenggarakan, namun hanya pada tataran teori tetapi pada tata cara pengurusan Tajhiz Mayit belum dipraktekkan secara langsung, sehingga diambil alih oleh Remaja Mesjid (Bilal) untuk melaksanakan. Adapun rancangan penelitian ini untuk memberikan rekomendasi Pembangunan Kota Medan Dalam Pengambilan Kebijakan pada Program dapat memperhatikan Pendidikan Keagamaan Generasi Millenial.